2016
DOI: 10.1371/journal.pone.0166398
|View full text |Cite
|
Sign up to set email alerts
|

Direct Unequal Cleavages: Embryo Developmental Competence, Genetic Constitution and Clinical Outcome

Abstract: ObjectiveTo investigate the prevalence, developmental potential, chromosomal constitution and clinical outcome of embryos with direct unequal cleavages (DUC).DesignA retrospective observational study.SettingAcademic Institution.Participant21,261 embryos from 3,155 cycles cultured in EmbryoScope®.ResultsThe total incidence of DUCs per embryo occupying the first three cleavages were 26.1%. Depending of the cell stage, DUC rate was 9.8% at first cleavage (DUC-1), 9.1% at second cleavage (DUC-2), and 3.7% at third… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
116
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(133 citation statements)
references
References 51 publications
(94 reference statements)
14
116
2
1
Order By: Relevance
“…Imaging of preimplantation embryos using both fixed- and live-cell microscopy supports a high frequency of multipolar mitosis during the cleavage stages, even for normally-fertilized 2PN zygotes [53, 54, 55]. The largest study to date, for example, observed that 26.1% of 21,261 2PN embryos exhibited tripolar mitosis [56], with previous studies obtaining similar, albeit slightly lower estimates (18% [54]; 17% [57]).…”
Section: Molecular Factors Contributing To Mitotic Errormentioning
confidence: 82%
“…Imaging of preimplantation embryos using both fixed- and live-cell microscopy supports a high frequency of multipolar mitosis during the cleavage stages, even for normally-fertilized 2PN zygotes [53, 54, 55]. The largest study to date, for example, observed that 26.1% of 21,261 2PN embryos exhibited tripolar mitosis [56], with previous studies obtaining similar, albeit slightly lower estimates (18% [54]; 17% [57]).…”
Section: Molecular Factors Contributing To Mitotic Errormentioning
confidence: 82%
“…For SC cycles, embryo selection for transfer was done using morphological grading alone. In TLI cycles, embryo selection was primarily based on morphological grading with a secondary use of avoidance criteria, namely, uneven cell division at the two-cell stage, 13,14 multinucleation at the fourcell stage, 15,16 direct first cleavage from one to three cells [≤5 hours t3-t2 (t3, time for the embryo to reach 3 cell stage and t2, time to reach 2 cell stage)] 17,18 and irregular cleavage including reverse cleavage. 19 A urine pregnancy test was done 18 days after oocyte retrieval and an early pregnancy transvaginal ultrasound was done at approximately 7 weeks' gestation.…”
Section: Embryo Transfer and Follow Upmentioning
confidence: 99%
“…Zhan et al [11] defined as the abrupt cleavage of one blastomere into three daughter blastomeres or an interval of cell cycles less than 5 h. Therefore, they describe direct unequal cleavage at first cleavage as DUC-1, at second cleavage as DUC-2, at third cleavage as DUC-3 and embryos exhibiting multiple DUCs as DUC-Plus. They found that the embryos fertilized with the sperm from epididymis, and testicles have significant higher DUP-1 percentage (13.6 vs. 11.4%).…”
Section: Special Markers In Time-lapse Systemmentioning
confidence: 99%